Conducive environment and completing assignments among the factors to celebrate Hari Raya on campus - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 6 May 2021 - The conducive environment on campus and busyness of completing assignments approaching next month’s exams has made some Universiti Malaysia Pahang (UMP) students to stay and celebrate Aidilfitri on campus.